Knowledge and preventive practices regarding Hepatitis B among nurses in some selected hospitals of Dhaka city, Bangladesh (South East Asia Journal of Public Health, 2015)
Hepatitis B is the most important infectious occupational hazard which the healthcare workers (HCWs) encounter. Healthcare personnel specially nursing staff represents a high risk population for HBV infection. The objective of the study was to assess the level of preventive practices regarding Hepatitis B among nurses and the factors associated with preventive practices. The study was conducted among 300 nurses both from public and private hospitals using a pretested structured questionnaire adopting a purposive sampling technique. The mean age of the respondents was 29.7±5.8 and majority of them (83.7%) were holding Diploma degrees with (83.3%) designated as staff nurse. About 59.7% were married and 94.3% were females. One third of the respondents (34.3%) were from public institution and 65.7% from private institution. It was revealed from the study that (67.3%) of the respondents had adequate level of knowledge on Hepatitis B but only half of them (49.3%) had good level of preventive practices. Bivariate analysis showed association between institution, income, age, religion, knowledge and level of preventive practice (P